The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/fsn3.1954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aroma‐active volatiles in an SDE extract of white tea

Abstract: White tea is a famous Chinese tea that is cooked at boiling point before drinking. The simultaneous distillation‐extraction (SDE) was used to collect volatile compounds during tea cooking. The SDE extract was dominated with green, floral, roasted and woody notes, and weak sweet note. There were 32 volatile compounds identified via gas chromatography–mass spectrometry analysis, and 19 of them had strong fragrance based on the gas chromatography‐olfactometry analyzed results. Hexanal, 2‐hexenal, cis‐3‐hexen‐1‐ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Rolling had no observable effects; however, the rolled leaf was easier to brew into a goodappearance tea, which may because the foliage cuticle and cell walls were destroyed during the rubbing process [14]. Furthermore, high-temperature pretreatment was conducive to form Maillard reaction products (MRPs), which markedly contribute not only to the aroma, taste and color but also to the antioxidant activity [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Rolling had no observable effects; however, the rolled leaf was easier to brew into a goodappearance tea, which may because the foliage cuticle and cell walls were destroyed during the rubbing process [14]. Furthermore, high-temperature pretreatment was conducive to form Maillard reaction products (MRPs), which markedly contribute not only to the aroma, taste and color but also to the antioxidant activity [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al 6 reported that 2-amylfuran was the main source of roasted aroma of white tea, its aroma intensity increased during the aging process of white tea. Similarly, Lin et al 11 found that 2-amylfuran was the main product during the drying process of white tea. Only one aroma-active compound which showed the aged fragrance, was sensed in WT-5, but unfortunately this compound was not identified.…”
Section: Gc-o Analysis Of Aroma Components In White Teamentioning
confidence: 87%
“…Ma et al 19 identified 24 aroma‐active components from Pu‐erh tea by using GC‐O and DF. Odor activity values (OAVs), 11 recombination and omission experiments have been applied to study key aroma‐active components in tea samples 17 . In our previous studies, phenylacetaldehyde, linalool, geraniol and 3‐ethyl‐2,5‐dimethylpyrazine were identified as the key aroma‐active compounds of high‐grade Dianhong tea (DHT) by OAVs and sensory‐directed aroma recombination and omission tests 20 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations